Estudo do desempenho de filtros ópticos interferométricos: interferômetro Mach-Zehnder de fibra óptica e ressonador óptico em anel - Lima, José Luiz Sousa (2006)
The nonlinear optical characteristics of a four-stage Mach-Zehnder interferometer and an optical ring resonator operating in soliton and quasi-soliton regime are investigated numerically. The Mach-Zehnder interferometer was constructed with ordinary telecommunication fiber and dispersion decreasing fiber considering a linear profile. The optical ring resonator waveguide was modeled with a nonlinear refractive index considering a increase linear profile. The transmission and compression factor of the switched pulses are analyzed. Results showed that the soliton and quasi-soliton transmissions of the four-stage MachZehnder interferometer are strongly dependent of the pump power. The crosstalk level is dependent on the pump power and the dispersion of the fiber. For high pump power the crosstalk is lower for the device with dispersion decreasing fiber in soliton regime. For this configuration the minimum crosstalk level (-22 dB) is obtained for pump power P = 2.7. In the quasi-soliton regime, in general the minimum crosstalk level is also lower for the four-stage Mach-Zehnder with dispersion decreasing fiber for high pump power but it is possible to obtain the minimum crosstalk level for the device with ordinary telecommunication fiber for high pump power. The extinction ratio is also very dependent on the pump power. It also degenerates with the increase of the pump power. For low pump power the four-stage Mach-Zehnder with ordinary telecommunication fiber and dispersion decreasing fiber presents a better extinction ratio compared to high pump power in soliton regime. In the quasi-soliton regime the better extinction ratio is obtained for the four-stage Mach-Zehnder with ordinary telecommunication fiber for high pump power. One can say that the operation of the device as an optical switch is not improving with the use of the dispersion decreasing fiber. However, for the multiplex/demultiplex operation, the proposed four-stage Mach-Zehnder constructed with dispersion decreasing fiber is showing improvements in the crosstalk levels in the soliton regime and, depending on the pump power, in the quasi-soliton regime as well. In the optical ring resonato study it was found that the ring waveguide loss lead to decrease of the short pulse transmission in both regimes, but maintaining the same nonlinear behaviour. The use of a nonlinear refractive index with linear increase profile lead to pulse compression or broadening, depending on pump power, in the soliton regime. In the quasi-soliton regime, it was observed no switched pulse deformation. This is an indication that the switched pulses have the same time duration of the input pulses in average. The results also showed that the transmission increases when the nonlinear refractive index with linear increase profile is used. Thus, the transmission decrease associated to the waveguide loss can be avoided. The transmission characteristics and optical pulse shaping of the four-stage Mach-Zehnder and optical ring resonato will be of interest in optical circuits and the all-optical communication systems in future.